2018
DOI: 10.3390/nu10111813
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Resveratrol Administration—Focus on Potential Biochemical Mechanisms in Cardiovascular Conditions

Abstract: Resveratrol (RV) is a natural non-flavonoid polyphenol and phytoalexin produced by a number of plants such as peanuts, grapes, red wine and berries. Numerous in vitro studies have shown promising results of resveratrol usage as antioxidant, antiplatelet or anti-inflammatory agent. Beneficial effects of resveratrol activity probably result from its ability to purify the body from ROS (reactive oxygen species), inhibition of COX (cyclooxygenase) and activation of many anti-inflammatory pathways. Administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 114 publications
(127 reference statements)
1
48
0
Order By: Relevance
“…Numerous studies reveal that the benefic effects of RSV are due to its potential to activate several important anti-inflammatory targets [119], although the exact mechanisms of action have not been clearly elucidated [120]. It was shown that the main target of RSV is SIRT-1, and its binding determines modifications of the SIRT-1 structure that enhances the binding of SIRT-1 to its substrates [121].…”
Section: Stilbenesmentioning
confidence: 99%
“…Numerous studies reveal that the benefic effects of RSV are due to its potential to activate several important anti-inflammatory targets [119], although the exact mechanisms of action have not been clearly elucidated [120]. It was shown that the main target of RSV is SIRT-1, and its binding determines modifications of the SIRT-1 structure that enhances the binding of SIRT-1 to its substrates [121].…”
Section: Stilbenesmentioning
confidence: 99%
“…Recent studies have reported that the blocking of BACE1 activity may prevent the progression of cerebral amyloid angiopathy associated with abnormalities in small brain vessels caused by Aβ aggregation [15]. Resveratrol (3,5,4 -trihydroxy-trans-stilbene), a polyphenol contained in red wine, peanuts, and some berries, is known for its anti-atherosclerotic, anti-inflammatory, antioxidant, and longevity-promoting properties [16]. There is ample evidence of its neuroprotective effects (Table 1).…”
Section: Aβ Peptides and Tau Proteinmentioning
confidence: 99%
“…Resveratrol has been shown to be particularly useful for the treatment of disorders such as Alzheimer's disease [16] because it prevents hippocampal neurodegeneration [29] and cognitive deficits [17]. Choi et al investigated the effect of resveratrol and its oligomers isolated from Paeonia lactiflora seed on beta-site APP-cleaving enzyme 1 (BACE-1) activity in vitro.…”
Section: Subject Of the Study Dose Effect Referencementioning
confidence: 99%
“…RES exerts anti-inflammatory and immunomodulating functions through activation of sirtuin-1 (Sirt-1) [87]. Sirt-1 operates by disrupting the TLR-4/NF-B/signal transducer and activator of transcription (STAT) pathway with decreased production of cytokines, platelet activating factor and histamine [88,89]. Sirt-1, as a deacetylase, plays an important role in immune tolerance and its abrogation leads to a spontaneous development of autoimmune disease [90,91].…”
Section: Regulation Of Immune Functions By Polyphenolsmentioning
confidence: 99%
“…RES -Activation of Sirt-1 with disruption of the TLR-4/NF-B/STAT pathway and decreased production of cytokines, PAF and histamine [87][88][89]; -Induction of AMP-activated protein kinase with increased levels of NAD+ which, in turn,…”
Section: Polyphenol Activitymentioning
confidence: 99%